Juventude rural: trajetórias de vida conectadas por um ideal social - Gonçalves, Jana Rossato (2015)
Given the emerging contemporary manifestations occurred around the world in recent years, there is youth participation in social marches. In Brazil the repercussions began in 2013 with the massive adherence of the Brazilian people, even though urban manifestations the rural protesters, specifically his youth, also joined the claims. This work has the public interest youth leaders from rural movements of Rio Grande do Sul, through them the objective is to understand their life stories, their relationships and their ideals, so, analyze their influence on the organization and participation of youth in rural mobilizations, in addition to observing the personal reasons encourage this leadership to remain the front of rural movements. The research has a qualitative approach, and the methodological processes constituted by literature search, application of semi-structured interviews to five rural youth leaders of different movements (Movimento dos Pequenos Agricultores (MPA), Federação dos Trabalhadores na Agricultura do Rio Grande do Sul (FETAG), Movimento Sem Terra MST, Pastoral da Juventude Rural (PJR) e Federação dos Trabalhadores na Agricultura Familiar da Região Sul (FETRAF SUL)) and finally, systematic observation in the demonstrations. So, can observe how the life experiences are linked to their current decisions on youth leadership and even having a strong tendency to reproduce the ideals of the older, is experiencing a break with these ideologies.